Combined use of infrared imaging techniques for the study of underlying features in the Santa Maria in Cosmedin altarpiece. (8th February 2021) - Mercuri, F.; Ceccarelli, S.; Orazi, N.; Cicero, C.; Paoloni, S.; Felici, A. C.; Matera, F.; Nuzzo, M.; Zammit, U.
Abstract : This paper presents a study carried out on the painted altarpiece preserved inside the Basilica of Santa Maria in Cosmedin, Rome, by combining three imaging techniques operating in the near‐ and mid‐infrared spectral ranges. The altarpiece has several pictorial layers and restorations, which have superimposed over time for stylistic adjustment and conservative purposes up to its present appearance. The results obtained in this study enable the detection of damage to the wooden support and the identification of pictorial features buried beneath the visible paint layer, thus providing significant information on the historical and artistic characterization of the artefact.